Gambaran Prevalensi Kelainan Penglihatan Binokular pada Anak Prasekolah di PAUD TAT Al-Arif, Bina Keluarga Balita (BKB) Mawar Calistung, dan TK Islam Al-Amin - Mariana, Wasti; Silaen, Desi Hartati; Lesmana, Michael Indra (Jurnal MedScientiae, 2025)
Binocular vision disorders in early childhood can affect visual development and learning ability. This study aims to determine the characteristics and prevalence of binocular vision disorders in preschool children at PAUD TAT Al-Arif K-Yana, BKB Mawar Calistung, and TK Islam Al-Amin. The study was conducted on 122 children aged 3–7 years using a quantitative descriptive design. The majority of respondents were female (58.2%) and aged between 5 and 6 years. Refraction test results showed that emmetropia was the most common condition in the right eye (61.5%) and left eye (60.7%). The Hirschberg test revealed that 13.9% of the children had exotropia, while 86.1% had a central and symmetrical light reflex. No heterophoria abnormalities were found, either at distance or near vision. This study highlights the importance of early screening to detect binocular vision disorders in preschool children so that early intervention can be carried out to prevent future visual developmental problems